2017
DOI: 10.1073/pnas.1702983114
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-mediated hypoxia functions as a signal for mosquito development

Abstract: Mosquitoes host communities of microbes in their digestive tract that consist primarily of bacteria. We previously reported that several mosquito species, including , do not develop beyond the first instar when fed a nutritionally complete diet in the absence of a gut microbiota. In contrast, several species of bacteria, including, rescue development of axenic larvae into adults. The molecular mechanisms underlying bacteria-dependent growth are unknown. Here, we designed a genetic screen around that identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
161
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 63 publications
4
161
3
2
Order By: Relevance
“…Differences in bacterial species diversity have been reported between larval stadia of Culex quinquefasciatus [60]. Studies of Aedes aegypti further show that substantial numbers of bacteria in the gut die at the end of each instar prior to molting, which provides opportunity for altering gut community composition in the succeeding instar [61]. Other patterns of note include that bacterial species diversity is consistently higher in mosquito larvae than adults [13, 15, 18, 47], and that diversity is lower in laboratory reared versus field collected mosquitoes of the same species [13, 14, 35].…”
Section: Composition Of the Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in bacterial species diversity have been reported between larval stadia of Culex quinquefasciatus [60]. Studies of Aedes aegypti further show that substantial numbers of bacteria in the gut die at the end of each instar prior to molting, which provides opportunity for altering gut community composition in the succeeding instar [61]. Other patterns of note include that bacterial species diversity is consistently higher in mosquito larvae than adults [13, 15, 18, 47], and that diversity is lower in laboratory reared versus field collected mosquitoes of the same species [13, 14, 35].…”
Section: Composition Of the Gut Microbiotamentioning
confidence: 99%
“…Functional assays supporting this hypothesis include the finding that gut hypoxia activates hypoxia-induced transcription factors (HIFs) in Ae. aegypti larvae which leads to activation of the insulin/insulin growth factor pathway, select mitogen activated kinases and other processes with essential growth functions [61, 70] (Figure 1). Transcriptome analysis also identifies several genes with functions in digestion and nutrient acquisition as additional targets that are potentially regulated by the gut microbiota or microbiota-induced hypoxia [71].…”
Section: Functional Roles Of the Gut Microbiota In Mosquito Larvaementioning
confidence: 99%
“…In Guangzhou, we designed three treatments: (a) water from natural flowerpots; (b) natural flowerpot water filtered by a 0.22-lm Millipore filter, which should have filtered >95% bacteria (Wang, Hammes, Boon, & Egli, 2007); and (c) ampicillin added to water from natural flowerpots, with a final antibiotic concentration of 100 lg/ ml. We used ampicillin as it is a wide-spectrum antibiotic and has been used in several studies on mosquito microbiota (Coon, Brown, & Strand, 2016;Coon et al, 2017). Fifty newly hatched larvae of the Ae.…”
Section: Ethics Statementmentioning
confidence: 99%
“…In this regard, there is some uncertainty as to whether these mosquitoes were truly axenic. In fact, a series of recent studies have reported that mosquitoes require a live bacterial symbiont for development 27,35,36 . Yet the studies describing the necessity of live bacteria generally ignored the role of microflora in supplying essential nutrients to the host.…”
Section: Introductionmentioning
confidence: 99%